2005
DOI: 10.1111/j.1601-5037.2005.00137.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral Hygiene and dental student's knowledge, attitude and behaviour in managing HIV/AIDS patients

Abstract: The human immunodeficiency virus (AIDS) and the acquired immunodeficiency syndrome (AIDS) have profoundly affected every aspect of the public health sector. The possibility of HIV transmission in the oral health care setting is very rare. Nonetheless, the oral health care environment has become a helpful setting for early detection, as most lesions of HIV infection present orally during the first stages of the disease. Willingness to treat patients with HIV/AIDS appears to be related to knowledge of the diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
63
1
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(77 citation statements)
references
References 4 publications
6
63
1
7
Order By: Relevance
“…Studies had shown that as the knowledge increases the willingness to treat HIV/AIDS patients increase. 3,4,14,30 In our study, 28.4% of students reported that they can do CPR to HIV patients and more male students were selfconfident about doing CPR. These results are extremely higher than those reported by others.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Studies had shown that as the knowledge increases the willingness to treat HIV/AIDS patients increase. 3,4,14,30 In our study, 28.4% of students reported that they can do CPR to HIV patients and more male students were selfconfident about doing CPR. These results are extremely higher than those reported by others.…”
Section: Discussionmentioning
confidence: 88%
“…12 These fears may cause inability to handle the treatment of HIV infected patients. 30 Adequate knowledge and positive attitude are the major criteria for treating HIV/AIDS patients. Studies had shown that as the knowledge increases the willingness to treat HIV/AIDS patients increase.…”
Section: Discussionmentioning
confidence: 99%
“…These results are similar to findings reported by Sadhegi et al [5]among Iranian dental students, Ryalat et al [6] among Jordanian dental students, and Brailo et al [7] among Croatian dental students. Several studies have shown that HIV/AIDS-related knowledge improves as one progress through the curriculum, and this improved knowledge has been correlated with improved and positive attitudes toward treating patients living with HIV/AIDS [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Most lesions of HIV/AIDS present orally during the initial stages of the disease, so dentists fall into the high risk category for cross contamination. 7 A major concern among dentists is cross-infection, from an infected patient to the dentist and further from the dentists to other patients in case of an accidental needle stick injury. It is unethical to deny treatment by a dental student or dentist to anyone infected with HIV.…”
Section: Introductionmentioning
confidence: 99%